INFECCIONES ASOCIADAS A LA ATENCIÓN DE SALUD EN RECIÉN NACIDOS DE MUY BAJO PESO DE UNA INSTITUCIÓN MATERNO PERINATAL - Velásquez Vásquez, Carlos (2025)
Introduction. Healthcare-associated infections are a frequent and severe complication in newborns with very low birth weight (NBVLBW). Objective. To describe the clinical and microbiological characteristics of these infections in newborns weighing between 500 and 1 499 grams at the National Maternal and Perinatal Institute. Methods. A descriptive, retrospective, and cross sectional study was conducted in Lima in 2024. A total of 266 newborns with confirmed diagnosis were included. Results. The infection rate was 13.9 %. Mortality reached 71.4 % in newborns weighing 500 to 999 grams and 19.8 % in those weighing 1 000 to 1 499 grams. Central venous catheters were involved in 68.7 % of cases. The most frequent pathogens were Staphylococcus coagulase-negative and Staphylococcus haemolyticus. Gram-negative bacilli showed higher lethality and resistance to multiple antimicrobial agents. Conclusion. Infections in NBVLBW are closely associated with the use of invasive devices and the presence of multidrug resistant pathogens, requiring improved prevention and surveillance.